2011
DOI: 10.1590/s1517-83822011000100028
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between API 50 CH and multiplex polymerase chain reaction for the identification of vaginal lactobacilli in isolates

Abstract: Identification of Lactobacillus sp. strains by phenotypic methods may lead to doubtful results possibly interfering in the reliability of the epidemiological and probiotics studies. Therefore this study aimed to determine the best methodology for the identification of the large diversity of lactobacilli species found in the vagina by comparing two techniques, one based on their biochemical profile and other employing molecular biology. A carbohydrate fermentation test (API 50 CH) was compared with multiplex po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
14
1
4
Order By: Relevance
“…lactis with an identity level of 73.5%, and was contrary to the BLAST analysis, which showed homology to the genus Weissella . Previous research has also shown a difference between biochemical test results using API 50 CHL and molecular analyses [19]; we have also found contradicting results when comparing the API kit to molecular technique. While in this study, the results of molecular analysis were Lactobacillus crispatus (32.6%), Lactobacillus jensenii (25%), and Lactobacillus gasseri (20.6%), the results of the API 50 CHL Kit analysis found Lactobacillus acidophilus (34.8%), L. crispatus (27.2%), and Lactobacillus fermentum (13%).…”
Section: Discussioncontrasting
confidence: 91%
“…lactis with an identity level of 73.5%, and was contrary to the BLAST analysis, which showed homology to the genus Weissella . Previous research has also shown a difference between biochemical test results using API 50 CHL and molecular analyses [19]; we have also found contradicting results when comparing the API kit to molecular technique. While in this study, the results of molecular analysis were Lactobacillus crispatus (32.6%), Lactobacillus jensenii (25%), and Lactobacillus gasseri (20.6%), the results of the API 50 CHL Kit analysis found Lactobacillus acidophilus (34.8%), L. crispatus (27.2%), and Lactobacillus fermentum (13%).…”
Section: Discussioncontrasting
confidence: 91%
“…The initial identification of the isolates was done by using gram staining, microscopic examination, and the carbohydrate fermentation test, using API 50 CH carbohydrate fermentation strips (bioMerieux, Craponne, France), and was based on phenotypical characteristics (Brolazo et al 2011). The results were analyzed according to the biochemical profiles registered in the APIweb ® database (bioMerieux).…”
Section: Identification Of Strainsmentioning
confidence: 99%
“…Similar incongruity situation reported for Lactobacillus crispatus which determined as Lactobacillus acidophilus by API test. The test may lead to provocative results and the reliability was being argued (Brolazo et al, 2011). Bahrami and Sjöholm (2016) supported that characterization by API 50 CH is not reliable enough by the fact that the database is not updated, and some new species are not available.…”
Section: Phenotypic and Genotypic Identification Of Lactobacillus Sppmentioning
confidence: 99%